Indonesian Throughflow, spatial–temporal variability, and its relationship to ENSO events in the Lombok Strait - Muhammad Zainuddin Lubis; Edriyan Situmorang; Andrean V. H. Simanjuntak; Nelly Florida Riama; Gumilang R. Pasma; Angga Dwinovantyo; Husnul Kausarian; Nyoman Metta N. Natih; Batara Batara; Kutubuddin Ansari; Punyawi Jamjareegulgarn (The Egyptian Journal of Aquatic Research, 2025)
• Significant fluctuations in ocean parameters due to ENSO events enhance our understanding of Lombok Strait dynamics. • El Niño impacts temperature and salinity variations, with a notable low during the 2015 event affecting local conditions. • Enhanced water flow in early 2018 indicates changing ocean circulation patterns linked to global warming effects. • The ITF plays a crucial role in regional and global ocean circulation, highlighting its importance in climate prediction. Understanding the interactions between ocean currents and climate variability is crucial for predicting future oceanic and climatic shifts in the Lombok Strait and beyond. Our study examines the Lombok Strait from 2013 to 2018, focusing on the impact of interannual and seasonal variability driven by climatic events such as the El Niño-Southern Oscillation. Our findings reveal significant fluctuations in oceanographic parameters, including temperature, salinity, and ocean currents. The lowest recorded temperature was ∼27.2 °C, and the minimum salinity was ∼32.3 psu, linked to the strong El Niño event in 2015, which altered local rainfall and evaporation patterns. Analysis of meridional and zonal velocities showed enhanced water flow, with maximum meridional velocities reaching around ∼0.04 m/s and zonal velocities peaking at ∼0.18 m/s in early 2018. Seasonal variations in sea surface height show higher values during warmer months, reflecting the influence of ENSO phenomena. The vertical distribution of salinity indicated stratification, with values ranging from ∼27.5 psu to ∼34.0 psu across different depths, corresponding to water density ranging from 22.50 σ θ to 24.0 σ θ , highlighting the interaction between Pacific and Indian Ocean waters. Water mass transport averages at 100 m and 200 m show values of −1.21 ± 0.97 Sv and −1.350 ± 1.069 Sv, with the lowest transport occurring during the summer at −1.97 Sv with a depth range of 0–100 m, suggesting robust outflow. Our findings underscore the critical role of the ITF in shaping regional oceanographic conditions and their implications for global climate dynamics.
Keywords: Oceanographic and Atmospheric Processes; Geological and Geophysical Studies; Marine and fisheries research